Proceedings of 2nd International Multi-Disciplinary Conference Theme: Integrated Sciences and Technologies, IMDC-IST 2021, 7-9 2022
DOI: 10.4108/eai.7-9-2021.2315380
|View full text |Cite
|
Sign up to set email alerts
|

Screening of extracellular polymeric substance producing bacteria isolated from environmental sources and testing their ability to seal fractures zones of oil reservoir rocks

Abstract: In this study, 21 environmental bacterial isolates isolated from different environmental sources in Basra Governorate identified phenotypically and genetically based on 16 rRNA gene sequence analysis were screened to reveal their ability to produce biopolymer based on the viscosity scale formed in the cultural media and use of Sudan Black stain. Six isolates showed their ability to produce biopolymer, and the two isolates of Bacillus licheniformis strain CC91, Bacillus thuringiensis strain LU3 recorded the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…BPPI‐14 and BPPI‐19 families, produced black grains when stained with Sudan Black 30 . According to the literature, Bacillus licheniformis strain CC91 and Bacillus thuringiensis strain LU3 oil reservoir rocks showed positive results for Sudan Black staining 31 . Sudan Black‐B has a significant affinity for lipid‐interacted biopolymers, which is important in the screening of PHA manufacturers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BPPI‐14 and BPPI‐19 families, produced black grains when stained with Sudan Black 30 . According to the literature, Bacillus licheniformis strain CC91 and Bacillus thuringiensis strain LU3 oil reservoir rocks showed positive results for Sudan Black staining 31 . Sudan Black‐B has a significant affinity for lipid‐interacted biopolymers, which is important in the screening of PHA manufacturers.…”
Section: Resultsmentioning
confidence: 99%
“…30 According to the literature, Bacillus licheniformis strain CC91 and Bacillus thuringiensis strain LU3 oil reservoir rocks showed positive results for Sudan Black staining. 31 Sudan Black-B has a significant affinity for lipid-interacted biopolymers, which is important in the screening of PHA manufacturers. Additionally, the microscopic data partially demonstrated that the isolate's intracellular lipid and biopolymer concentration was connected to its cytoplasmic components and structural specifications.…”
Section: Sudan Black Stainingmentioning
confidence: 99%